Post-communism and some problems of interpretation of the marxist tradition - Gutorov, Vladimir A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article examines the actual aspects of the interpretation of the Marxist tradition in post-communist political and philosophical discourse. It is noted that from the 1990s many of the emerging ideas, which became the property of a new social philosophy of post-communism, were of great importance both for the development of principles of analysis that are not devoid of ideological bias and for the main vectors of politics. At the same time, philosophers and scholars who turned to the revision of the origins of the social philosophy of Marxism, quite often and very persistently tried to justify the ideas that arose in the 1920s (N. A. Berdyaev, K. Manheim and others).
Keywords: Marxism; post-communism; social philosophy; political ideology; historical tradition